SENCE OF HUMOR AND THEMATIC PREFERNCES IN JOKES AT PREADULT AND MATURE AGE - R V Ershova; R Z Kiyamova (Peoples' Friendship University of Russia (RUDN University), 2016)
The research contains the analysis of the existing conceptions of the sense of humor, its psychological determinants and manifestations; this enables to justify the necessity of its study as a system personality trait from a position of structural-functional approach. The results of a comparative study of the sense of humor of the preadult and mature age representatives are analysed. The common links of the sense of humor components possessed by the preadult and mature age representatives with the choice of humor direction thematic constructs are examined and described. The specific links of the sense of humor components possessed by the pre - adult age representatives (such as socio-centricity, meaningfulness, awareness, subjectivity, vigor, inertia, sthenicity) with the choice of humor direction thematic constructs (such as gender interrelation, harmful habits, money, fashion, career, social woes, human stupidity) are described. The typical links of the sense of humor components possessed by the mature age representatives (such as egocentricity, subjectivity, vigor, externality) with the choice of humor direction thematic constructs (such as gender interrelation, fashion, family friction, social woes, lack of talent in art) are disclosed. In the end the article presents the findings, describing the psychological features of certain theme humor perception by the people of different ages.